Perancangan Arsitektur Aplikasi Learning Management System Di Universitas Slamet Riyadi - Tigus Juni Betri; Ema Utami; Hanif Al Fatta (IJAI (Indonesian Journal of Applied Informatics), 2017)
E-Learning is one of the solutions in current learning system. Implementation of electronic-based learning, teaching and learning process can be more varied at the same time can eliminate the saturation of learners. Implementation of E-Learning or well known as Learning Management System at Slamet Riyadi University Surakarta, so far not running maximally. Among the most fundamental features available are not in accordance with the standards of application of E-Learning. The solution for this problem is better to design a new system. The development model used is to adopt the Borg and Gall model with the outline of the prototype application. In developing this prototype, data collection needs of users is done to relevant stakeholders, namely Information Technology Education courses, students and lecturers as end users as well as experts in the field of IT and curriculum. The results showed, based on the questionnaire to end users can be concluded that the prototype offered can be accepted among the end users and experts. This is shown from the statistical results of the analysis of the influence between variables that are formulated. Hypothesis of influence between variables most or dominant produce prototype acceptable.